HOW ISLAMIC BANKING CAN GROW IN YOUTH: EMPIRICAL EVIDENCE FROM URBAN CENTER - Khawaja, Hussain; Ahmed, Dr. Kazi Afaq (The journal of contemporary issues in business and government, 2021)
The study explores how Islamic banking can effectively and professionally use social media applications to persuade youth towards the Islamic banking system. It is evident from the previous literature that Islamic financial institutions are not maximizing the potential of social media. Therefore, this study conducted an exploratory research design interviews youth of Hyderabad to analyze how social media platform can be useful in imparting knowledge sharing. There were 15 interviews conducted with students having undergraduate, graduate, and post- graduate qualifications. The result of the study highlights four themes. The social media application will initiate relationship building, customer engagement, Social Media networks for creating Customer Preferences, Lack of Social Media Marketing Efforts by Islamic Banking. This study is beneficial for Islamic financial institutions in innovating their marketing strategies towards technologically advanced networks. The effective and effective utilization of social media applications will upsurge the customer reach.